Challenges Facing A B2B E-Commerce Export Trade Portal: A Case Study Of Asiaep.com - Sun, Lim Chiang (2001)
This paper attempts to provide some guidelines as to the challenges members of a B2B E-Commerce portal in Malasyia asiaep.com. The paper draws mainly literatures and experiences of E-Commerce in the Internet.